Forwarding in vehicular named data networking VNDN - Laggoun, Khadidja Fatima Zahra; Saihi, Khadidja; Abdelhafidi, Fatima Zahra, Directeur de thèse (Laghouat : Université Amar Telidji - Département d'informatique, 2024)
Vehicular Named Data Networking (VANET-NDN) architecture prioritizes content names over content locations in vehicular ad hoc networks (VANETs). However, VANET-NDN forwarding strategies currently face broadcast storms and network fragmentation issues. To address these problems, our focus is on studying and improving existing protocols such as SAFT-VNDN. Our first step involves enhancing these protocols, followed by simulating SAFT-VNDN and its enhancement (referred to as new-SAFT) using the Ns2 simulator. The simulation results demonstrate that new-SAFT performs better than SAFT-VNDN in terms of end-to-end delay and packet delivery ratio.